Alone but together: Adult distance study through computer conferencing - Daniel V. Eastmond (Adult Education Research Conference, 1994)
Computer conferencing allows students to interact with each other and the instructor in structured communications from geographically dispersed locations, participating in the conference by personal computer and modem connection at any time of the day. This qualitative study investigated the following: (a) distance student life situations and reasons for seeking a degree as adults; (b) student perceptions of the computer conference and its role in learning; (c) the learning approaches students employ in this instructional environment; and (d) the nature of group discussions by diverse participants and the formation of on-line relationships.